Microencapsulated quercetin and Bifidobacterium animalis attenuate enteric gliosis and mucosal immune activation in the ileum during colorectal carcinogenesis - Sabrina Silva Sestak; João Victor Kuller; Lucas Casagrande; Carla Cristina de Oliveira Bernardo; Lídia Rodrigues Cícero; Fabiana Galvão da Motta Lima; César Agostinho Ferreira; Tania Cristina Alexandrino Becker; Waldiceu Aparecido Verri Junior; Juliana Vanessa Colombo Martins Perles; Jacqueline Nelisis Zanoni (PharmaNutrition, 2026)

Microclimate monitoring and modelling in a regenerating urban environment: Milano (Italy) - Luca Gallia; Stefano Basiricò; Shamila Haddad; Thomas Parkinson; Aysu Kuru; Akisha Nomoto; Roberto Colombo; Riccardo Castellanza; Federico Agliardi (Urban Climate, 2026)

Design of 3D-printed hydroxyapatite intervertebral fusion cages in a patient specific framework - Anna De Cet; Martina Colombo; Luca D’Andrea; Ilaria Rota; Luigi La Barbera; Pasquale Vena; Dario Gastaldi (Medical & Biological Engineering & Computing, 2026)
Fusion surgery involves replacing degenerated intervertebral discs with artificial implants, usually composed of titanium alloys or PEEK, requiring bone grafting to assist tissue growth. This study aims to evaluate numerically 3D-printed porous ceramic implants as a bioactive alternative. Clinical computed tomographies of an adult patient were used to reconstruct the geometry and to assign mechanical properties to L1 and L2 vertebrae, utilizing a patient-specific anisotropic micromechanics-based model. The influence of different microstructural choices on a porous hydroxyapatite-based scaffold was analysed through finite element analysis, simulating standing and flexion. The analyzed scaffolds included: microstructured Face Centered Cubic (FCC) and Kelvin-based devices with uniform porosity (75%), and a Voronoi microstructured scaffold with uniform (75%) and graded porosity (60% external, 90% internal). Homogenized models were considered as a potential strategy to reduce computational costs. The FCC geometry and graded Voronoi proved more mechanically resistant to failure. Homogenized mechanical properties simplified the model, but didn’t accurately represent microstructural behaviour and local mechanical failure couldn’t be suitably identified. Patient-specific models allowed for a more accurate representation of mechanical stresses, leading to a reduced risk of structural failure. Hydroxyapatite proves to be a promising material for 3D-printed lumbar interbody fusion cages, able to provide primary stability.

Conversion of municipal biowaste into value-added products toward a circular bioeconomy: bridging the gap between laboratory-scale and full-scale implementation - José Manuel Alejandro Cerdán; Tatiana Kimura Kodama; G. H. D. Oliveira; Lucas Tadeu Fuess; Júlia Fonseca Colombo Andrade; Aldo Roberto Ometto (Clean Technologies and Environmental Policy, 2026)
Scaling-up municipal biowaste conversion technologies to industrial levels is essential for advancing clean and sustainable technologies and addressing significant technical, economic, and environmental challenges associated with urban organic waste management. Studies that explore technological gaps across the upstream, midstream, and downstream processing stages of biorefineries are critical for transforming biowaste into value-added products. This study aims to fill these gaps through a systematic literature review following the PRISMA guidelines and utilizing the Technology Readiness Level (TRL), which enabled the selection of 88 cases subsequently analyzed using descriptive and content analysis. The main findings show that anaerobic digestion has achieved full commercial maturity (TRL 9), while acidogenic fermentation remains mostly at TRL 6–7, and other pathways such as microbial protein or holocellulase production are still at early stages (TRL 3–4). High-value products, including polyhydroxyalkanoates (PHA) and succinic acid, are clustered at TRL 6–7, typically demonstrated at pilot scale, whereas hydrochar from hydrothermal carbonization has progressed up to TRL 8–9. Companies and projects confirm the feasibility of integrating biological, chemical, and thermal pathways into biorefineries, spanning a wide range of TRLs and showcasing their potential within the circular bioeconomy. Key gaps persist in scaling downstream processes for product purification, reducing costs, addressing feedstock variability, and optimizing pretreatment. By synthesizing experimental evidence with industrial demonstrations and sustainability assessments, this study provides a comprehensive perspective on how municipal biowaste can be converted into both non-fuel bioproducts and biofuels, thereby supporting circular bioeconomy strategies for future environmental policies. Graphical Abstract

Predicting acute developmental toxicity of chemicals in embryos of the African clawed frog (Xenopus laevis): Calibration and validation of regression-based quantitative structure activity relationship models for hazard assessment of chemicals in anuran amphibians - Christian Novello; Matteo Riccardo Di Nicola; Jean Lou CM Dorne; Erika Colombo; Edoardo Luca Viganò; Manuel E. Ortiz-Santaliestra; Nynke Kramer; Edoardo Carnesecchi; Anna Melina Steinbach; Ivano Eberini; Antony Williams; Emilio Benfenati; et al. (Toxicology Letters, 2026)

Seas of Renewal: Turning Sea Urchin Waste into Polyhydroxynaphtoquinone-Collagen Biomaterials for Regenerative Medicine - Giordana Martinelli; Stefania Marzorati; Margherita Roncoroni; Luciano Magro; Matteo Brilli; Giangiacomo Beretta; Graziano Colombo; Luca Melotti; Anna Carolo; Giulia Zivelonghi; Stefano Farris; Marco Patruno; et al. (Marine Biotechnology, 2025)
Chronic wounds and skin ulcers pose significant challenges to healthcare systems globally, necessitating innovative approaches to accelerate healing processes. Biomaterial-based therapies have emerged as promising solutions for tissue regeneration. This study focuses on valorization of sea urchin waste toward the development and characterization of collagen-based scaffolds added with polyhydroxynaphthoquinone (PHNQ) antioxidants, successfully incorporated into biomaterials at optimal ratio, enhancing scaffold stability and integrity. Water uptake, mechanical properties, and degradation kinetics of the composite scaffolds were evaluated and compared with controls. Biocomposites were also tested for cytotoxicity. Results indicate that composite scaffolds exhibit superior chemical stability and slower degradation rates, attributed to strong interactions between collagen and PHNQs. This aspect was explored also through in silico investigations by means of tight binding molecular dynamics methods. It has been found that a covalent bond forms between the selected collagen representative and one PHNQ. Furthermore, the antioxidant activity of PHNQs was retained in the composite scaffolds, providing additional therapeutic benefits under the perspective application of regenerative medicine. Normal human dermal fibroblasts (NHDF) exposed to the combination of collagen and PHNQs remained viable. Overall, these findings highlight the potential of sea urchin food waste in a valorization chain, offering added value through the production of collagen-based composite scaffolds.

Factors controlling the water quality of rock glacier springs in European and American mountain ranges - Stefano Brighenti; Nicola Colombo; Thomas Wagner; Michael Pettauer; Nicolas Guyennon; Karl Krainer; Monica Tolotti; Michela Rogora; Luca Paro; Sandra M. Steingruber; Chantal Del Siro; Cristian Scapozza; et al. (Science of The Total Environment, 2024)

Thermal effects and biological response of breast and pancreatic cancer cells undergoing gold nanorod-assisted photothermal therapy - Leonardo Bianchi; Sara Baroni; Gabriela Paroni; Martina Bruna Violatto; Giulia Yuri Moscatiello; Nicolò Panini; Luca Russo; Fabio Fiordaliso; Laura Colombo; Luisa Diomede; Paola Saccomandi; Paolo Bigini (Journal of Photochemistry and Photobiology B: Biology, 2024)

Experimental study on coalescer efficiency for liquid-liquid separation - Igor Matteo Carraretto; Davide Scapinello; Riccardo Bellini; Riccardo Simonetti; Luca Molinaroli; Luigi Pietro Maria Colombo; Giampaolo Manzolini (Desalination, 2024)

The VERA software: Implementation of the acute fish toxicity endpoint and its application to pharmaceutical compounds - Erika Colombo; Edoardo Luca Viganò; Giuseppa Raitano; Anna Lombardo; Alberto Manganaro; Alessio Sommovigo; Emilio Benfenati (Chemosphere, 2024)

Fostering action perspectives to support crop diversification: Lessons from 25 change-oriented case studies across Europe - Margot Leclère; Lenn Gorissen; Yvonne Cuijpers; Luca Colombo; Mirjam Schoonhoven-Speijer; Walter A.H. Rossing (Agricultural Systems, 2024)

Reversing the trend of agrobiodiversity decline by co-developing food chains with consumers: A European survey for change - Yuna Chiffoleau; Tara Dourian; Géraldine Enderli; Dalia Mattioni; Grégori Akermann; Allison Loconto; Francesca Galli; Gulyás Emese; Zsófia Perényi; Luca Colombo; Sonia Massari; Dominique Desclaux (Sustainable Production and Consumption, 2024)

Radar observation and recontruction of Cosmos 1408 fragmentation - Andrea Muciaccia; Luca Facchini; Marco Felice Montaruli; Giovanni Purpura; Roberto Detomaso; Camilla Colombo; Mauro Massari; Pierluigi Di Lizia; Alessandra Di Cecco; Luca Salotti; Germano Bianchi (Journal of Space Safety Engineering, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Arhgap22 Disruption Leads to RAC1 Hyperactivity Affecting Hippocampal Glutamatergic Synapses and Cognition in Mice - Anna Longatti; Luisa Ponzoni; Edoardo Moretto; Giorgia Giansante; Norma Lattuada; Maria Nicol Colombo; Maura Francolini; Mariaelvina Sala; Luca Murru; Maria Passafaro (Molecular Neurobiology, 2021)
Rho GTPases are a class of G-proteins involved in several aspects of cellular biology, including the regulation of actin cytoskeleton. The most studied members of this family are RHOA and RAC1 that act in concert to regulate actin dynamics. Recently, Rho GTPases gained much attention as synaptic regulators in the mammalian central nervous system (CNS). In this context, ARHGAP22 protein has been previously shown to specifically inhibit RAC1 activity thus standing as critical cytoskeleton regulator in cancer cell models; however, whether this function is maintained in neurons in the CNS is unknown. Here, we generated a knockout animal model for arhgap22 and provided evidence of its role in the hippocampus. Specifically, we found that ARHGAP22 absence leads to RAC1 hyperactivity and to an increase in dendritic spine density with defects in synaptic structure, molecular composition, and plasticity. Furthermore, arhgap22 silencing causes impairment in cognition and a reduction in anxiety-like behavior in mice. We also found that inhibiting RAC1 restored synaptic plasticity in ARHGAP22 KO mice. All together, these results shed light on the specific role of ARHGAP22 in hippocampal excitatory synapse formation and function as well as in learning and memory behaviors.

2D and 3D numerical models to evaluate trabecular bone damage - Federica Buccino; Chiara Colombo; Daniel Hernando Lozano Duarte; Luca Rinaudo; Fabio Massimo Ulivieri; Laura Maria Vergani (Medical & Biological Engineering & Computing, 2021)
The comprehension of trabecular bone damage processes could be a crucial hint for understanding how bone damage starts and propagates. Currently, different approaches to bone damage identification could be followed. Clinical approaches start from dual X-ray absorptiometry (DXA) technique that can evaluate bone mineral density (BMD), an indirect indicator of fracture risk. DXA is, in fact, a two-dimensional technology, and BMD alone is not able to predict the effective risk of fractures. First attempts in overcoming this issue have been performed with finite element (FE) methods, combined with the use of three-dimensional high-resolution micro-computed tomographic images. The purpose of this work is to evaluate damage initiation and propagation in trabecular vertebral porcine samples using 2D linear-elastic FE models from DXA images and 3D linear FE models from micro-CT images. Results show that computed values of strains with 2D and 3D approaches (e.g., the minimum principal strain) are of the same order of magnitude. 2D DXA-based models still remain a powerful tool for a preliminary screening of trabecular regions that are prone to fracture, while from 3D micro-CT-based models, it is possible to reach details that permit the localization of the most strained trabecula. Graphical abstract

Bees and pesticides: the research impact and scientometrics relations - Raiza Abati; Amanda Roberta Sampaio; Rodrigo Mendes Antunes Maciel; Fernanda Caroline Colombo; Gabriela Libardoni; Lucas Battisti; Everton Ricardi Lozano; Nédia de Castilhos Ghisi; Fabiana Martins Costa-Maia; Michele Potrich (Environmental Science and Pollution Research, 2021)

Characterization of “Mais delle Fiorine” (Zea mays L.) and nutritional, morphometric and genetic comparison with other maize landraces of Lombardy region (Northern Italy) - Luca Giupponi; Valeria Leoni; Federico Colombo; Elena Cassani; Monika Hejna; Luciana Rossi; Roberto Pilu (Genetic Resources and Crop Evolution, 2021)
The loss of agrobiodiversity is a topic of global impact. On a local scale, Lombardy, in the Alpine macro-Region, has lost more than 78% of its plant agrobiodiversity. Only four maize ( Zea mays L. subsp. mays ) landraces of Lombardy are registered in the European Register of Conservation Varieties. However, there are other maize landraces in Lombardy such as “Mais delle Fiorine”, which was characterized from an agronomic, morphometric, nutritional and genetic point of view in this research and then compared with the four other landraces already registered (“Spinato di Gandino”, “Rostrato Rosso di Rovetta”, “Scagliolo di Carenno” and “Nero Spinoso”). “Mais delle Fiorine” resulted richer in starch (81% ± 1.6) and zinc (35.8 ± 9.1 mg Kg −1 ) and lower in phosphorus (3256.7 ± 204.2 mg Kg −1 ). The kernels in the five landraces also differ in the mean shape that is obovate without beak. A genetic distinction between “Mais delle Fiorine” and the other varieties was observed, and in particular compared to “Nero Spinoso”, while “Scagliolo di Carenno” and “Rostrato Rosso di Rovetta” showed great similarities. As regards agronomical trials, “Mais delle Fiorine” can grow from the Po Valley (90 m a.s.l.) to the mountain environments of the Seriana Valley (also over 900 m a.s.l.) without significant differences in grain yield. In addition, this landrace would seem able to tolerate environments where there is a greater probability of water stress.

Bioindicators and biomonitoring: honeybees and hive products as pollution impact assessment tools for the Mediterranean area - Stefano Girotti; Severino Ghini; Elida Ferri; Luca Bolelli; Roberto Colombo; Giorgia Serra; Claudio Porrini; Stefano Sangiorgi (Euro-Mediterranean Journal for Environmental Integration, 2020)
The global range of the environmental quality issues we all face necessitates integrated action from all of the countries that suffer from a particular environmental issue. We must be able to obtain data on the presence of pollutants and their effects on biota from any territory, regardless of its environmental, infrastructural, social, and economic conditions. Biomonitoring utilizes organisms and natural materials to obtain this information. In particular, the honeybee is a ubiquitous, easy-to-breed organism with great mobility. Its body, which is covered with hairs, picks up materials and particulates that it encounters in the environment. Therefore, bees are highly effective accumulators of materials from the soil, vegetation, air, and water. These characteristics mean that the honeybee is both a bioindicator and a passive bioaccumulator organism, making it an ideal agent for easily monitoring vast areas inexpensively, even in regions where infrastructure is scarce. In this short review, we summarize the main targets of the honeybee-based monitoring campaigns that have been carried out to date, highlighting the results obtained in assessments of organic and inorganic pollution performed by coupling more modern technologies with this long-standing practice. It is hoped that this review will make scientists more aware of the incredible potential of these delicate organisms to provide data that could prove useful in the management of environmental issues.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Neutralization of extracellular NAMPT (nicotinamide phosphoribosyltransferase) ameliorates experimental murine colitis - Giorgia Colombo; Nausicaa Clemente; Andrea Zito; Cristiano Bracci; Federico Simone Colombo; Sabina Sangaletti; Elena Jachetti; Davide Giuseppe Ribaldone; Gian Paolo Caviglia; Luca Pastorelli; Marco De Andrea; Samuele Naviglio; et al. (Journal of Molecular Medicine, 2020)

Assessing the impact of ground ice degradation on high mountain lake environments (Lago Nero catchment, Swiss Alps) - Cristian Scapozza; Nicola Deluigi; Monica Bulgheroni; Sebastián Pera Ibarguren; Maurizio Pozzoni; Luca Colombo; Fabio Lepori (Aquatic Sciences, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Access to agricultural land in peri-urban spaces: social mobilisation and institutional frameworks in Rome and Valencia - Pedro Cerrada-Serra; Luca Colombo; Dionisio Ortiz-Miranda; Stefano Grando (Food Security, 2018)

Trans-splicing of plastid rps12 transcripts, mediated by AtPPR4, is essential for embryo patterning in Arabidopsis thaliana - Luca Tadini; Roberto Ferrari; Marie-Kristin Lehniger; Chiara Mizzotti; Fabio Moratti; Francesca Resentini; Monica Colombo; Alex Costa; Simona Masiero; Paolo Pesaresi (Planta, 2018)

Recent trends in chloride and sodium concentrations in the deep subalpine lakes (Northern Italy) - Michela Rogora; Rosario Mosello; Lyudmila Kamburska; Nico Salmaso; Leonardo Cerasino; Barbara Leoni; Letizia Garibaldi; Valentina Soler; Fabio Lepori; Luca Colombo; Fabio Buzzi (Environmental Science and Pollution Research, 2015)

Models to predict the start of the airborne pollen season - Consolata Siniscalco; Rosanna Caramiello; Mirco Migliavacca; Lorenzo Busetto; Luca Mercalli; Roberto Colombo; Andrew D. Richardson (International Journal of Biometeorology, 2015)

Trends in Surface Water Chemistry in Acidified Areas in Europe and North America from 1990 to 2008 - Øyvind A. Garmo; Brit Lisa Skjelkvåle; Heleen A. de Wit; Luca Colombo; Chris Curtis; Jens Fölster; Andreas Hoffmann; Jakub Hruška; Tore Høgåsen; Dean S. Jeffries; W. Bill Keller; Pavel Krám; et al. (Water, Air, & Soil Pollution, 2014)

TGF-beta specifically enhances the metastatic attributes of murine lung adenocarcinoma: implications for human non-small cell lung cancer - Paula Fernanda Vázquez; María José Carlini; María Cecilia Daroqui; Lucas Colombo; Mercedes Liliana Dalurzo; David Eduardo Smith; Julieta Grasselli; María Guadalupe Pallotta; Marcelo Ehrlich; Elisa Dora Bal de Kier Joffé; Lydia Puricelli (Clinical & Experimental Metastasis, 2013)

Effects of Nicotine on Cardiovascular Remodeling in a Mouse Model of Systemic Hypertension - E. Sage Colombo; Joshua Davis; Mehran Makvandi; Mario Aragon; Selita N. Lucas; Michael L. Paffett; Matthew J. Campen (Cardiovascular Toxicology, 2013)

Thirty Years of Chemical Changes in Alpine Acid-Sensitive Lakes in the Alps - Michela Rogora; Luca Colombo; Fabio Lepori; Aldo Marchetto; Sandra Steingruber; Ombretta Tornimbeni (Water, Air, & Soil Pollution, 2013)

Immunostimulatory and cytotoxic activities of Indigofera suffruticosa (Fabaceae) - Flávia C.M. Lopes; Tamara R. Calvo; Lucas L. Colombo; Wagner Vilegas; Iracilda Z. Carlos (Natural Product Research, 2011)

The porcine TBC1D1 gene: mapping, SNP identification, and association study with meat, carcass and production traits in Italian heavy pigs - Luca Fontanesi; Michela Colombo; Lucia Tognazzi; Emilio Scotti; Luca Buttazzoni; Stefania Dall’Olio; Roberta Davoli; Vincenzo Russo (Molecular Biology Reports, 2011)